Evidence That GRIN2A Mutations in Melanoma Correlate with Decreased Survival - D'mello, Stacey Ann N.; Flanagan, Jack U.; Green, Taryn N.; Leung, Euphemia Y.; Askarian-Amiri, Marjan E.; Joseph, Wayne R.; McCrystal, Michael R.; Isaacs, Richard J.; Shaw, James H.; Furneaux, Christopher E.; During, Matthew J.; FInlay, Graeme J.; et al. (Frontiers in Oncology, 2014)
Previous whole-exome sequencing has demonstrated that melanoma tumors harbor mutations in the GRIN2A gene. GRIN2A encodes the regulatory GluN2A subunit of the glutamate-gated N-methyl-d-aspartate receptor (NMDAR), involvement of which in melanoma remains undefined. Here, we sequenced coding exons of GRIN2A in 19 low-passage melanoma cell lines derived from patients with metastatic melanoma. Potential mutation impact was evaluated in silico, including within the GluN2A crystal structure, and clinical correlations were sought. We found that of 19 metastatic melanoma tumors, four (21%) carried five missense mutations in the evolutionarily conserved domains of GRIN2A; two were previously reported. Melanoma cells that carried these mutations were treatment-naïve. Sorting intolerant from tolerant analysis predicted that S349F, G762E, and P1132L would disrupt protein function. When modeled into the crystal structure of GluN2A, G762E was seen to potentially alter GluN1–GluN2A interactions and ligand binding, implying disruption to NMDAR functionality. Patients whose tumors carried non-synonymous GRIN2A mutations had faster disease progression and shorter overall survival (P < 0.05). This was in contrast to the BRAF V600E mutation, found in 58% of tumors but showing no correlation with clinical outcome (P = 0.963). Although numbers of patients in this study are small, and firm conclusions about the association between GRIN2A mutations and poor clinical outcome cannot be drawn, our results highlight the high prevalence of GRIN2A mutations in metastatic melanoma and suggest for the first time that mutated NMDARs impact melanoma progression.